The Patient Experience: Informing Practice through Identification of Meaningful Communication from the Patient’s Perspective - Grocott, Angela (Healthcare (Basel), 2018)
(1) Background: There is limited empirical knowledge concerning aspects of healthcare that contribute to a good patient experience from the patient’s perspective and how patient feedback informs service development. (2) Aim: To examine the issues that influence the effectiveness of communication on patient satisfaction, experience and engagement, in an acute National Health Service (NHS) setting, through identification of the patient’s requirements and expectations. (3) Method: Data was gathered from a large teaching hospital using a Friends and Family Test (FFT) and a communication specific survey. Both surveys captured patient narrative to identify predominant influences to explain the quantitative responses. (4) Results: The key priorities for patients are involvement in their care and receiving the right amount of information to support this. However, the delivery of compassionate care was identified as having the most influence on the likelihood of patients to recommend an acute NHS Trust. (5) Conclusion: The findings support a broader understanding of the constituents of an all-encompassing patient experience from the patient’s perspective. (6) Implications: healthcare organizations need to focus their resources on how to improve patient/provider communication to support patients to be true partners in their care.